Identification of Flavonoid Compounds in Ethanol Extract of Majapahit plant (Crescentia cujete) Leaves and their Potential as Anticancer - Martha, Rahma Diyan; Fatimah, Fatimah; Danar, Danar; Parbuntari, Hesty (CHEESA: Chemical Engineering Research Articles, 2023)
The Majapahit plant is commonly found in Indonesia but is rarely used due to a lack of information about its potential. One of the secondary metabolites commonly found in this plant are flavonoids. Therefore, this study aims to determine the distribution of flavonoid compounds in the Majapahit plant, particularly their potential as anticancer activty. Leaf material from Majapahit plants was extracted using the maceration technique, while the flavonoid compounds in the extract were identified using LCMS (Shimadzu LCMS-8040 LC/MS). The identification results showed that about 97 compounds were detected, including 14 flavonoids. The flavonoid compounds found include Quercetin, Chlorogenic acid, Kaempferol 3-O rhamnoside, Acacetin 7-rutinoside, Fortunellin, Kaempferol 3-[6"-(3-hydroxy-3-methyl glutarl) glucoside], Didymin, Diosmin, Hesperidin, Rutin, Citrusoside C, Citrusoside D, Narirutin 4'-glucoside, and Kaempferol 3-[6"-(3-hydroxy-3-methylglutaryl)glucoside] -7-glucoside. The highest composition of the identified flavonoid compounds was found in Kaempferol 3-O rhamnoside, with a 3.90%